2020
DOI: 10.1007/s11162-020-09594-9
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Shared Vision for Change: Moving toward Inclusive Empowerment

Abstract: Shared vision is an important process for change projects, serving to amplify success, increase participation, and erode the divide between project leaders and constituents. Yet there are few empirical examinations of the process of building shared vision within academic departments. Using focus groups and participant observation, this study examines shared vision development within 13 large-scale change projects in engineering and computer science higher education. We find that teams of faculty, staff, admini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…The perceived isolation negatively impacts on the professional experience and success of the novice leader [42]. This is consistent with the claim of Sheninger that instructional leaders must articulate and share their school vision to ensure effective school performance by creating a leadership synergy from the teachers primarily [43]…”
supporting
confidence: 78%
“…The perceived isolation negatively impacts on the professional experience and success of the novice leader [42]. This is consistent with the claim of Sheninger that instructional leaders must articulate and share their school vision to ensure effective school performance by creating a leadership synergy from the teachers primarily [43]…”
supporting
confidence: 78%
“…The quantitative and qualitative data was also consistent in its support for the perceived acceptability, appropriateness and feasibility of the specialized vestibular physiotherapy service in the ED. Developing a shared vision or shared goals for change is an effective strategy for promoting buy-in and participation whenever practice transformation is attempted (31). However, in this study many participants reported feeling unsure about the implementation plan and evaluation plan for specialized vestibular physiotherapy in the ED.…”
Section: Discussionmentioning
confidence: 77%
“…Team formation is a process, and the team is not a fixed, static entity [7], [11], [12]. During the process of team formation, members co-create an interactive, shared definition of the team that includes a sense of solidarity with teammates [13], [14] and a shared vision for change [9], [11], [15]. Creating a unified team voice and developing a sense of group agency are critical mechanisms in the process of team formation [2], [9], [14], [16].…”
Section: Unified Voice and Group Agencymentioning
confidence: 99%